Peran Literasi Keuangan dan Gaya Hidup dalam Mempengaruhi Perilaku Keuangan Mahasiswa di Kota Semarang - Nabila, Fawwaz Afaf Muti; Nugraheni, Krisnawati Setyaningrum (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The purpose of this research is to understand and analyze the influence of financial literacy and lifestyle on the financial behavior of students in Semarang City. The research was conducted in Semarang City, Central Java. The study employs a quantitative method with a survey research design. The research population consists of all students in Semarang City. The sampling technique used is accidental sampling with a sample size of 108 individuals. Data collection was done through the distribution of questionnaires, while data analysis was conducted using multiple linear regression analysis. The results of the research are: 1) financial literacy has a significant and positive influence on financial behavior with a t-value of 12.099 > t-table value of 1.98282, 2) lifestyle has a significant and positive influence on financial behavior with a t-value of 2.493 > t-table value of 1.98282, 3) financial literacy and lifestyle have a simultaneous effect on financial behavior with an F-value of 213.843 > F-table value of 3.93, 4) financial literacy and lifestyle influence financial behavior by 80.5%, while the remaining 19.5% is influenced by external factors not discussed in this study.